Gaining a (tube) foothold – trends and status following two decades of the long-spined echinoid Diadema setosum (Leske, 1778) invasion to the Mediterranean Sea - Zirler, Rotem; Leck, Lynn Angele; Farkash, Tamar Feldstein; Holzknecht, Martina; Kroh, Andreas; Gerovasileiou, Vasilis; Huseyinoglu, Mehmet Fatih; Jimenez, Carlos; Resaikos, Vasilis; Yokeş, Mehmet Baki; Bronstein, Omri (Frontiers in Marine Science, 2023)
The Eastern Mediterranean Sea is an exceptional habitat. Its relative isolation and distinct characteristics create a unique ecosystem recognized as a marine biodiversity hot spot, where one-fifth of the species are endemic. Yet, native Mediterranean biodiversity is under increasing threat, mainly due to massive alien species invasions of Indo-Pacific origin. To date, more than 800 non-indigenous species have been reported in the Eastern Mediterranean Sea, justifying its reputation as one of the most severely affected habitats in the world in terms of marine biological invasions. Here we summarized the Mediterranean invasion dynamics of the long-spined echinoid Diadema setosum (Leske, 1778), one of the most ubiquitous Indo-Pacific sea urchin species. We show an alarming exponential population growth of D. setosum throughout the Eastern Mediterranean since 2018, following more than a decade of ‘invasion lag’ since its first detection in 2006. Molecular analyses illustrate the presence of a single genetic D. setosum clade in the Mediterranean Sea – corresponding to the Arabian Peninsula clade of this species, reinforcing the notion of a Red Sea origin. Our data support the current working hypothesis that the initial introduction of D. setosum occurred in the Northern Levantine Basin from which it gradually expanded in both north-west and south-east trajectories – in contrast to a stepping-stone hypothesis of gradual advancement from the opening of the Suez Canal. Demographic data of D. setosum along the Israeli Mediterranean coastline reveals a well-established population of broad size distributions, from juveniles to adult individuals of remarkably large size. Additionally, we provide evidence of the reproductive capacity of D. setosum in its new environment. Due to the magnitude of Diadema’s ecological footprint, it poses a severe threat to the entire Eastern Mediterranean Sea, including the Levantine Basin and South Aegean Sea, calling for rapid and coordinated action at both national and regional scales.